TELAAH PEDAGOGIK PEMBEBASAN PAULO FREIRE DI ERA REVOLUSI INDUSTRI 4.0 - Pratiwi, Eka Fauziah (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
These technological advances in the 4.0 industrial revolution were already beginning to apply to education in Indonesia. This article has the goal of building teaching skills or pedagogies in teaching with a digit-based curriculum. Using literacy and content analysis, the author explained that potential educators should be able to keep pace with technological progress without abandoning their established cultural values. The use of technology in this educational world is supposed to help students and teachers can together have an active role in the learning process. This theory harmonizes with Paulo Freire's view of humanistic education based on the similarities between humans. In summary, educators are expected to be able to teach by giving as much knowledge as possible without repressing the thinking or character of their students.